Penelope Crumb - Stout, Shawn K.; Docampo, Valeria, 1976- (New York : Puffin Books, 2013)
Fourth-grader Penelope Crumb's large nose leads to a family discovery.
Booklist
Horn Book
Publisher's Weekly
Booklist, August 2012
Bulletin (Center for Children's books), October 2012
Horn Book, July 2012
Keywords: Families -- Juvenile fiction; Grandfathers -- Juvenile fiction; Nose -- Juvenile fiction; Family life -- Fiction; Grandfathers -- Fiction; Nose -- Fiction; Family life -- Fiction; Grandfathers -- Fiction; Nose -- Fiction